Comparison of TNF-α Levels in Alcoholic Liver Disease Patients with and without Hepatitis: A Cross-sectional Study in Coastal Karnataka, India - TM Anuraghi; Krishnamoorthy Srilatatha; Jinsha Fathima; Yassir Shaheena (National Journal of Laboratory Medicine)
Introduction: Alcohol-induced liver injury triggers inflammatory reactions through pro-inflammatory cytokine Tumour Necrosis Factor-α (TNF-α). The estimation of TNF-α would provide valuable information on the degree of activation of immune system and inflammation in the liver cells, which is crucial in the diagnosis as well as prognosis of alcoholic hepatitis. Aim: To compare TNF-α levels in Alcoholic Liver Disease (ALD) patients with or without hepatitis. Materials and Methods: This cross-sectional study was conducted at Yenepoya Medical College Hospital, Mangaluru, Karnataka, India from October 2021 to June 2022. The study included 52 patients diagnosed with Alcoholic Liver Disease (ALD), aged between 45-75 years which were equally divided into two groups (n=26 each): ALD with hepatitis and ALD without hepatitis. The diagnosis of hepatitis was made based on the De Ritis ratio (>2) along with a history of alcohol consumption. The Liver Function Test (LFT) was estimated using the automated system. Child-Pugh (CP) score was assessed by scoring serum albumin, total bilirubin, Prothrombin Time (PT), ascites, and grades of hepatic encephalopathy. The TNF-α was estimated by the Enzyme Linked Immuno Absorbent Assay (ELISA). The LFT, CP score, and TNF-α levels were compared between ALD patients with or without hepatitis using Independent sample t-test. Results: All the study participants were male, with the median age of those with alcoholic hepatitis being 50.23 years. Around 65% of them had severe liver dysfunction with higher CP scores (p-value=0.001). Platelet count was significantly lower in alcoholic hepatitis, resulting in prolonged PT. Patients with alcoholic hepatitis had significantly high levels of bilirubin (p-value=0.006), aspartate transaminase (p-value=0.001), alkaline phosphatase (p-value=0.001), and TNF-α (p-value=0.005). Conclusion: The study concluded that the patients of ALD have elevation of TNF-α levels, when they progress to or have episodes of active hepatitis.